2017
DOI: 10.1002/gps.4672
|View full text |Cite
|
Sign up to set email alerts
|

Prospective relationship between objectively measured light physical activity and depressive symptoms in later life

Abstract: Background:The use of self-report measures of physical activity is a serious methodological weakness in many studies of physical activity and depressive symptoms. It is still equivocal whether light physical activity protects older adults from depressive symptoms.Objective: This study aimed to explore whether objectively measured light physical activity, independent of sedentary and moderate-to-vigorous activity, is associated with a reduced risk of subsequent depressive symptoms in older adults. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
2
36
1
Order By: Relevance
“…[1][2][3] Research has tended to focus on moderate-to-vigorous physical activity (MVPA; ie, approximately ≥3 metabolic equivalents [METS]), although there is a lack of evidence on health benefits of light physical activities (LPA; ie, activities ranging between 1.5 and <3 METS) such as casual walking, lifting lightweight objects, light household chores or yard works, and stretching. 4,5 According to the estimates from the US National Health and Nutrition Examination Survey, time spent in devicemeasured LPA among adults (7.8 h/d) is much higher than those spent in MVPA (0.2 h/d). 6 LPA appears to have potential to increase daily physical activity energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Research has tended to focus on moderate-to-vigorous physical activity (MVPA; ie, approximately ≥3 metabolic equivalents [METS]), although there is a lack of evidence on health benefits of light physical activities (LPA; ie, activities ranging between 1.5 and <3 METS) such as casual walking, lifting lightweight objects, light household chores or yard works, and stretching. 4,5 According to the estimates from the US National Health and Nutrition Examination Survey, time spent in devicemeasured LPA among adults (7.8 h/d) is much higher than those spent in MVPA (0.2 h/d). 6 LPA appears to have potential to increase daily physical activity energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been described as a positive health behavior that can reduce the risk of subsequent depressive symptoms in later life by prospective studies . As a plausible mechanism, physical activity is considered to activate specific biological pathways; increase a sense of mastery, a sense of self‐worth, or number of social contacts; or distract from negative thoughts .…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been described as a positive health behavior that can reduce the risk of subsequent depressive symptoms in later life by prospective studies. [14][15][16] As a plausible mechanism, physical activity is considered to activate specific biological pathways; increase a sense of mastery, a sense of self-worth, or number of social contacts; or distract from negative thoughts. 17 Moreover, a prospective study of over 3 years of follow-up reported that even low levels of physical activity and walking were associated with lower depressive and anxiety symptoms in older women.…”
mentioning
confidence: 99%
“…Although many studies found a relation between overall levels of physical activity and depressive symptoms 10,11,36,41,42 of which most were measured by self-report physical activity, a few studies that used objectively measured physical activity also did not nd this relationship 14,43 . The results of this study suggest that differences in physical activity in depression (when measured objectively) might not lie in the total amount of activity, but rather in the day-to-day differences in patterns of physical activity.…”
Section: Discussionmentioning
confidence: 99%